DEVELOPMENT OF INNOVATION MANAGEMENT AT THE ENTERPRISES OF METALLURGY - A. E. Nikiforov; L. M. Kravets (Литьë и металлургия)
The development of innovation management at the enterprises of metallurgy is shown.